Coefficient-based accounting of Net Additions to Stock (NAS) and associated embodied energy for Eryaman, Ankara. Issue 2 (4th May 2021) - Reçber, Nazife; Şengül, Hatice
ABSTRACT: Considering the large spatial scale of urban development in metropolitan areas, data quality and resolution are very important in determining accurate material stock figures. There is currently a limited but growing number of studies that employ bottom-up accounting based on high resolution spatial data rather than analysis of aggregated city-level data as was employed in relatively older studies. This study contributes to this literature by assessing Net Additions to Stock (NAS) in Eryaman, Ankara, Turkey using GIS software NETCAD. It was determined that NAS on a per capita basis for the early and mature stages of urban development correspond to 1, 800 and 240 ton/capita, respectively. These figures of material stock are greater than that of many other cities owing to high Material Intensity Coefficients (MICs) of reinforced concrete and masonry structures prevalent in the study area. When energy demand for construction materials was considered, it was determined that the material stock has a total embodied energy of 21.2 TJ in 2015. The findings of the study, in line with previous findings in the literature for other urban areas, point to the need for focusing on material selection as functional elements and intensified eco-efficiency efforts for sustainable urban development.Not Started Completed Rejected.